Phylogenetic structure and biogeography of the Pacific Rim clade of Sphagnum subgen. Subsecunda: haploid and allodiploid taxa. (11th June 2015) - Shaw, A. Jonathan; Shaw, Blanka; Johnson, Matthew G.; Devos, Nicolas; Stenøien, Hans K.; Flatberg, Kjell I.; Carter, Benjamin E.
<x xml:space="preserve">Abstract</x> Although it is an uncommon distribution in seed plants, many bryophytes occur around the Pacific Rim of north‐western North America and eastern Asia. This work focuses on a clade of peatmosses (Sphagnum) that is distributed around the Pacific Rim region, with some individual species found across the total range. The goals were to infer divergent phylogenetic relationships among haploid species in the clade, assess parentage of allopolyploid taxa, and evaluate alternative hypotheses about inter‐ and intraspecific geographical range evolution. Multiple data sets and analyses resolved an 'Alaska' clade, distributed across western North America, eastern China and Japan, and an 'Asia' clade that includes western Chinese, Thai, Korean, eastern Chinese and Japanese lineages. Allopolyploids have arisen at least four times in the Pacific Rim clade of Sphagnum subgen. Subsecunda; it appears that all allopolyploid origins involved closely related haploid parental taxa. Biogeographical inferences were impacted by topological uncertainty and especially by the biogeographical model utilized to reconstruct ancestral areas. Most analyses converge on the conclusion that the ancestor to this clade of Pacific Rim Sphagnum species was widespread from Alaska south to eastern Asia, but a northern origin for the Alaska subclade was supported by one of the two biogeographical models we employed, under which it was robust to phylogenetic uncertainty.